Moisture absorption behaviour of sugar palm fiber reinforced epoxy composites - Leman, Z.; Sapuan, S. M.; Saifol, A.M.; Maleque, Md. Abdul; Ahmad, M.M.H.M. (Elsevier, 2008)
In engineering practice, moisture absorption test is generally used for quality control purposes and to measure the degradation of the quality for the composite materials. The objectives of this study are to investigate the value of Fickian difusivity constant, moisture equilibrium content and the correction factor the natural fiber composites.